ASSESSMENT OF SOME HEAVY METALS IN CANNED FISHES FOR HUMAN HEALTH - Caglar, Metin; Canpolat, Ozgur (Parlar Scientific Publications (P S P), 2016)
Information on the metal content in canned fish is important to ensure that the fish consumed is safe for human consumption. In this study, the concentrations of some heavy metals in were determined in seven different brands (A, B, C, D, E, F and G) of canned tuna fish samples available in local food markets of Elazig (Turkey). Only copper (Cu), iron (Fe), zinc (Zn) and cadmium (Cd) were detected in canned tuna fish samples analysed. Nickel (Ni), and chromium (Cr) were found to be undetectable levels in the all samples. The heavy metals were found to be in the range of 13.08-22.35 mg/kg for iron, 9.05-16.76 mg/kg for zinc, 0.23-0.38 mg/kg for copper and 0.046-0.058 mg/kg for cadmium. These results show that heavy metal levels in canned tuna fish samples were under the dangerous limits given by WHO and FAO and their is no any risk for public health by consuming.
Keywords: Canned fish; heavy metals; food safety